Growth Hormone and Neuronal Hemoglobin in the Brain—Roles in Neuroprotection and Neurodegenerative Diseases - Walser, Marion; Svensson, Johan; Karlsson, Lars; Motalleb, Reza; Åberg, Maria; Kuhn, H Georg; Isgaard, Jörgen; Åberg, N David (Frontiers in Endocrinology, 2021)
Abstract In recent years, evidence for hemoglobin (Hb) synthesis in both animal and human brains has been accumulating. While circulating Hb originating from cerebral hemorrhage or other conditions is toxic, there is also substantial production of neuronal Hb, which is influenced by conditions such as ischemia and regulated by growth hormone (GH), insulin-like growth factor-I (IGF-I), and other growth factors. In this review, we discuss the possible functions of circulating and brain Hb, mainly the neuronal form, with respect to the neuroprotective activities of GH and IGF-I against ischemia and neurodegenerative diseases. The molecular pathways that link Hb to the GH/IGF-I system are also reviewed, although the limited number of reports on this topic suggests a need for further studies. In summary, GH and/or IGF-I appear to be significant determinants of systemic and local brain Hb concentrations through mediating responses to oxygen and metabolic demand, as part of the neuroprotective effects exerted by GH and IGF-I. The nature and quantity of the latter deserve further exploration in specific experiments.